Screening for abdominal aortic aneurysm in the world and in Russia - T. V. Balakhonova; A. I. Ershova; V. V. Genkel; E. V. Garbuzova; L. Yu. Drozdova; A. V. Svetlikov; R. S. Akchurin; S. A. Shalnova; S. A. Boytsov; O. M. Drapkina (Российский кардиологический журнал)
Despite the global trend towards a decrease in the prevalence of abdominal aortic aneurysm (AAA), this disease remains one of the sudden death causes in the elderly. This necessitates the need to conduct screening studies, the effectiveness and feasibility of which has been proven in large studies, including population-based ones, and meta-analyses. The traditional and most optimal screening method is ultrasound examination. According to the guidelines of different countries, the indications for abdominal aorta ultrasound vary. Today in Russia there is no accurate data on the prevalence of AAA, while the target group for screening has not been defined, and therefore the country needs to conduct large population studies to study its prevalence and risk factors, as well as to calculate indicators of the clinical and economic effectiveness of implementation AAA screening programs.